The implementation of a mobile application to decrease occupational sitting through goal setting and social comparison - Tsaoane, Moipone Lipalesa (Rhodes University, Faculty of Science, Department of Computer Science)
Background: Feedback proves to be a valuable tool in behaviour change as it is said to increase compliance and improve the effectiveness of interventions. Interventions that focus on decreasing sedentary behaviour as an independent factor from physical activity are necessary, especially for office workers who spend most of their day seated. There is insufficient knowledge regarding the effectiveness of feedback as a tool to decrease sedentary behaviour. This project implemented a tool that can be used to determine this. To take advantage of the cost-effectiveness and scalability of digital technologies, a mobile application was selected as the mode of delivery. Method: The application was designed as an intervention, using the Theoretical Domains Framework. It was then implemented into a fully functioning application through an agile development process, using Xam- arin.Forms framework. Due to challenges with this framework, a second application was developed using the React Native framework. Pilot studies were used for testing, with the final one consisting of Rhodes University employees. Results: The Xamarin.Forms application proved to be unfeasible; some users experienced fatal errors and crashes. The React Native application worked as desired and produced accurate and consistent step count readings, proving feasible from a functionality standpoint. The agile methodology enabled the developer to focus on implementing and testing one component at a time, which made the development process more manageable. Conclusion: Future work must conduct empirical studies to determine if feedback is an effective tool compared to a control group and which type of feedback (between goal-setting and social comparison) is most effective.
Keywords: Sedentary behavior; Sitting position; Feedback; Mobile apps; Behavior modification; Agile software development